A qualitative study of facilities and their environmental performance - (:unkn) unknown (Emerald Group Publishing Ltd., 2004)
Improving indoor environmental conditions and, thus, health standards will have a direct impact on the performance of the employees and, thus, organisations and on the wealth of the community. The indoor air quality, lighting, ergonomics, acoustics and health complaints scales are widely used to determine building performance levels. The research model was tested using responses from 362 employees in 25 diverse hospitals. The results indicate that building comfort level assessments play a critical role in influencing the health complaints and building general sufficiency level judgements of the employees. These judgements differ from each other for the hospital groups classified according to the ownership criteria. This study will support a better evaluation of development policies of workplace environmental conditions by managers. © Emerald Group Publishing Limited.
Keywords: Buildings; Environmental health and safety; Facilities; Performance levels